The Effect of Cutting Material on the Propagation Succes of Sungkai (Peronema canescen Jack.) and Cutting Potential Provided by Hedge Orchad - NFN Sahwalita (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2017)
Sungkai (Peronema canescen Jack.) is a potential spesies in the development of the forest plantation. The forest plantation require the seeds of quality and the cover of every season planting. This research was conducted at KHDTK Kemampo, Banyuasin District, South Sumatra province. This article aims of a variety of node to quality of the Peronema canescen Jack. seedlings at nursery and widely hedge orchards needed a source of the propagation material. The research was designed in randomized block design with 4 node variation treatments were N1: 2 node; N2: 1 node; N3: 2 node the cutting and N4: 1 node the cutting and the material needs propagation calculated from the node that can be used as the seedlings. Totally of stump, height, diameter and survival rate were used parameters of seedling growth.The result showed that 1 node the cutting treatment give the growth good of the seeds with survival rate 100%. The potency of hedge orchard of 1 ha widely will be able to meet the needs of the seedlings of 1,344 hectare of forest plantation in every season planting.